Perhitungan Mutu Air Laut Di Perairan Sekitar Pembangkit Listrik Tenaga Uap - Eka Wardhani; Dhea Alya Hanifa (Jurnal Serambi Engineering, 2024)
One of the causes of the decline in sea water quality is due to industrial activities near sea waters, one of which is Steam Power Plants where the cooling system activity process of the generating equipment becomes a problem because it is thrown into the sea at high temperatures. Based on this, it is necessary to calculate the status of sea water quality in order to find out whether sea water quality has decreased due to the PLTU's activities. The aim of this research is to determine the quality profile of sea water and determine the impact of activities in the surrounding waters at several monitoring points around the waters of the Steam Power Plant. The way to determine or status method for water quality is with a pollution index based on Decree of the Minister of Environment Number 115 of 2003. Water quality can be assessed based on the classification of pollutant indicators, the pollutant index value around the Steam Power Plant in 2020 Quarter II is 7.86 at the point 6. Meanwhile, in 2021 and 2022 there will be a decline in every quarter and at all points, for determining quality status refers to Minister of the Environment Regulation No. 2003 No. l115, in 2020 Quarter II, the quality status of sea water around the waters of the Steam Power Plant was included in the moderately polluted category and in both 2021 and 2022 the quality status of sea water around the waters of the Steam Power Plant was included in the lightly polluted category